Cellular-level structure imaging in rat colon ex vivo and in vivo using micro-optical coherence tomography (μOCT) - Yu, Xiaojun (2017)
The feasibility of a constructed high-resolution OCT for cellular-level structures imaging in rat colon was evaluated for the first time. Imaging results demonstrated that OCT could be a viable tool for intestinal mucosa structures imaging.